Th17 serum cytokines in relation to laboratory-confirmed respiratory viral infection: A pilot study - Antalis,E.; Spathis, A.; Kottaridi,C.; Kossyvakis,A.; Pastellas,K.; Tsakalos,K.; Mentis, A; Kroupis, C.; Tsiodras,S. (J.Med.Virol., 2019)
BACKGROUND: Th17 cytokines are associated with modulation of inflammation and may be beneficial in clearing influenza infection in experimental models. The Th17 cytokine profile was evaluated in a pilot study of respiratory virus infections. METHODS: Consecutive patients with symptoms of respiratory tract infection visiting the emergency department of a tertiary care hospital during the winter influenza season of 2014 to 2015 were evaluated. CLART PneumoVir kit, (GENOMICA, Madrid, Spain) was used for viral detection of all known respiratory viruses. Th17 cytokine profile was evaluated with the MILLIPLEX MAP Human TH17 Magnetic Bead Panel (Millipore Corp., Billerica, MA). Correlation of the TH17 profile with viral detection was performed with univariate and multivariate analysis. RESULTS: Seventy-six patients were evaluated (median age 56 years, 51.3% female); a respiratory virus was identified in 60 (78.9%) patients; 45% had confirmed influenza. Influenza A (H3N2) correlated with higher levels of granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin 1beta (IL-1beta), IL-17A, IL-17E, IL-17F, IL-21, IL-22, and IL-23 (P < 0.05 by analysis of variance [ANOVA]) compared with respiratory syncytial virus (RSV). Parainfluenza virus (PIV) similarly had higher levels of GM-CSF, IL-1b, IL-17A, IL-22 compared with those detected in RSV, influenza B and any other virus infection ( P < 0.05; ANOVA). Increasing age (beta-coefficient = 1.11, 95% CI, 1.04-1.2, P < 0.01) as well as IL-17A levels (beta-coefficient = 1.03, 95% CI, 1.001-1.05, P = 0.04) predicted hospital admission. CONCLUSION: Main Th17 cell effector cytokines were upregulated in laboratory-confirmed A(H3N2) influenza and PIV. Excessive amounts of Th17 cytokines may be implicated in the pathogenesis and immune control of acute influenza and PIV infection in humans and may predict the severity of disease
IS - 1096-9071 (Electronic) IS - 0146-6615 (Print) IS - 0146-6615 (Linking) LA - eng PT - Journal Article RN - 0 (Cytokines) RN - 0 (Interleukin-17) RN - 0 (Interleukin-23) RN - 0 (Interleukins) RN - MKM3CA6LT1 (interleukin-21) SB - IM
Keywords: Adult; Aged; analysis; Blood; Cytokines; Diagnosis; Female; Greece; Humans; immunology; Interleukin-17; Interleukin-22; Interleukin-23; Interleukins; Male; Middle Aged; Pilot Projects; Respiratory Tract Infections; Spain; Th17 Cells; virology; Virus Diseases